Behavioral Experience-Sampling Methods in Neuroimaging Studies With Movie and Narrative Stimuli - Jääskeläinen, Iiro P.; Ahveninen, Jyrki; Klucharev, Vasily; Shestakova, Anna N.; Levy, Jonathan (Frontiers in Human Neuroscience, 2022)
Movies and narratives are increasingly utilized as stimuli in fMRI, MEG, and EEG studies. Emotional reactions of subjects, what they pay attention to, what they memorize, and their cognitive interpretations are all examples of inner experiences that can differ between subjects during watching of movies and listening to narratives inside the scanner. Here, we review literature indicating that behavioral measures of inner experiences play an integral role in this new research paradigm via guiding neuroimaging analysis. We review behavioral methods that have been developed to sample inner experiences during watching of movies and listening to narratives. We also review approaches that allow for joint analyses of the behaviorally sampled inner experiences and neuroimaging data. We suggest that building neurophenomenological frameworks holds potential for solving the interrelationships between inner experiences and their neural underpinnings. Finally, we tentatively suggest that recent developments in machine learning approaches may pave way for inferring different classes of inner experiences directly from the neuroimaging data, thus potentially complementing the behavioral self-reports.